PENGARUH LEVERAGE, PROFITABILITAS DAN LIKUIDITAS TERHADAP KUALITAS LABA PADA PERUSAHAAN SUB SEKTOR RETAILING - Wina Permata Ramadhani; Muhammad Rivandi (Journal of Innovation Research and Knowledge, 2025)
Earnings quality is an important indicator for evaluating a company's earnings results and ensuring that the financial information presented is accurate and reliable for decision making by management and investors. The aim of this research is to determine empirically and significantly the influence of leverage, profitability and liquidity on the profit quality of companies in the retailing sub-sector for the period 2021 - 2023. This research uses a quantitative approach and the sampling technique used is purposive sampling. This research used a sample of 16 companies observed for 3 years, resulting in a total of 48 data. Data obtained from the Indonesian Stock Exchange (BEI) https://www.idx.co.id/id. Data processing uses E-Views version 9.0. The results of this research explain that leverage has no effect on earnings quality, profitability has a significant negative effect on earnings quality and liquidity has no effect on earnings quality.